Income mobility in the developing world: Recent approaches and evidence - Himanshu; Peter Lanjouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper examines income mobility in developing countries. We start by synthesizing findings from the available evidence on relative mobility and poverty dynamics. We then describe evidence on economic mobility obtained via synthetic panels constructed from cross-section data. We echo earlier literature in pointing to substantial movement across income classes by households over time: poverty is not inevitably a chronic condition. However, less clear are the factors driving the observed 'churning'. In an attempt to make headway, we consider the story of economic mobility in one village in northern India over seven decades. We describe patterns of poverty dynamics and economic mobility in the village, and we highlight some of the processes that have been important in driving these patterns. While this in-depth case study does not permit inferences to broader populations, it may provide a reference point against which findings from studies elsewhere can be compared.
Keywords: C15; I32; O15; 330; Entwicklungsländer; Developing countries; Fallstudie; Case studies